Suburbal Residents’ Environmental Culture and its Connection with the Formation of Municipal Solid Waste Dumps - Doroshenko, D. O.; Shyrokostup, S. M. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2018)
The problem of environmental pollution is becoming increasingly relevant every year. It manifests itself not only at the global but also at the local level. The most common cause of these problems is the neglect of the population to the environment. This can be clearly seen in the suburban area, where there is a problem of accumulation of solid household waste and the occurrence of unauthorized dumps. In the suburban area, unlike the city, there are no necessary tools for managing the streams of solid waste. Purpose. To investigate the correlation between the level of environmental awareness of the population of the Babai village and the existing problem of landfills in this village. Results. In the course of the study, the main groups-subjects of economic activity that affect the state of the environment were identified. The survey revealed a low interest of local population in environmental issues. The introduction of environmental practices by residents of the Babai village is due more to economic than environmental reasons. Recommendations were developed for each of the identified groups of stakeholders based on the obtained data. Conclusions. In order to address the problem of solid waste accumulation in Babai, administrative, social and educational groups of decisions were proposed. Administrative decisions include an agreement with the shipping company for the creation of municipal solid waste collection system. Social decisions include awareness campaigning measures aimed at raising the level of environmental culture of the local population. Educational solutions include conducting environmental education work with pupils of the Babai secondary school. Compliance with the selected recommendations by the public and government will help to solve the existing environmental problems.